Contestation and Coexistence: The Puritanical Da’wah of Luthfi Bashori and Its Implication for Nahdlatul Ulama - Rofiq, Ahmad Choirul; Sugiyar; Saepudin Mashuri (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2025)
Luthfi Bashori is a cleric of Nahdlatul Ulama with his controversial ASWAJA Garis Lurus (Straight Line) or NU Garis Lurus. However, no in-depth research has examined his da’wah and its implications for the NU. This library research study utilized documentation and observation of Bashori's da’wah in digital media. This study focused on the objectives, strategies, themes, and reactions to Bashori's da’wah. The theory of action motives, conflict theory, and da’wah perspectives guided data analysis. This research asserted that the purpose of Bashori's da’wah is to maintain the ASWAJA (Ahlus Sunnah Wal Jama’ah) of KH. Muhammad Hasyim Asy’ari, as well as fortifying Muslims from secularism, pluralism, liberalism, Shia, and Wahhabism. According to Weber’s theory, Bashori da’wah is motivated by religious values and purposive goals. His strategy of da’wah varied depending on the context. His themes of da’wah contained Islamic law, theology, morality, and political issues. The content of his da’wah is based on his understanding of the Qur'an and hadith. In addition to getting pro and con responses from Nahdliyin, his da’wah implied strengthening religious opposition and internal contestation in the NU. This research uncovered the puritanical religious da’wah in the NU. It revealed that the NU managed internal conflict with coexistence among groups of dissenting viewpoints due to the moderation paradigm.